THE ROLE OF THE INVESTMENT COMPONENT IN THE INNOVATIVE DEVELOPMENT OF TERRITORIES - E. Merzlyakova; A. Ovchinnikova (Вестник Северо-Кавказского федерального университета)
Investment activity largely determines the activation of innovation processes in the territories. The article uses the methodology of correlation and regression analysis to identify the tightness of the relationship between indicators that characterize innovation and investment processes in the region. The distribution of the Central Federal district regions by the level of innovation susceptibility to the volume of investment in fixed assets and foreign investment was made. In addition, the degree of influence of investment on the volume of innovative products in the Kursk region was revealed. The conclusion is made about the signiicant role of the investment component in the innovative development of territories. The mechanisms for stimulating the attraction of investment resources in order to increase the level of innovative development of the Kursk region are outlined.